(untitled) (Fiep Bulletin - online, 2017)
It is a fact that the fights were always present in the history of mankind in many ways: learning of attack and defensetechniques, as a means of survival, are linked to training and military formations, is considered as physical exercise, often areinterrelated to the cultural, religious and philosophical training from many countries and above all is seen as a source of wisdom oflife to many teachers and students. This articleaims to discuss through the genetic epistemology why some teachers of wrestlingand martial arts in our present present aggressive behavior and violence inside and outside the tatami mats and other teachers didnot present that kind of behavior. This work seeks to present reflections on the influence of teachers’ behavior on students. Themethodology used is qualitative, of basic nature and explanatory nature. We conclude that the teachers that show aggressivebehavior and violence still does not demonstrate a moral autonomy and along that moral construction were aggregated moralvalues to their moral personality, so teachers who present disciplinarians behaviors aimed at pacification invariably present in hispersonality moral values.